Punishment for Perpetrators with Special Needs (Disability) in the Current Criminal Process : Pemidanaan terhadap Pelaku Berkebutuhan Khusus (Disabilitas) dalam Proses Pidana Saat Ini - Rahayu , Lutfah (Universitas Muhammadiyah Sidoarjo, 2024)
General background of this research emphasizes the state's vital role in ensuring the rights of persons with disabilities within the legal framework, particularly in criminal proceedings. The specific background highlights the challenges these individuals face in the justice system, often encountering biases that hinder their access to justice. The knowledge gap identified indicates a lack of comprehensive research on the legal treatment and punishment of offenders with disabilities in Indonesia, especially under the new Criminal Code. This research aims to analyze punishment implementation for such offenders and the collaboration between judges and psychiatrists for fair legal processes. The results reveal that a normative descriptive method, incorporating expert assessments and judicial discretion, is crucial for adjudicating these cases. The novelty lies in proposing a collaborative approach that encourages judges to consider legal principles alongside individual circumstances. The implications advocate for systemic reforms to enhance protections and treatment of persons with disabilities in the criminal justice system, ensuring equitable rights and justice for all citizens. This study contributes to the dialogue on legal reform and social justice, urging policymakers to foster an inclusive legal environment. Highlights: Emphasizes the importance of integrating expert assessments in legal proceedings for offenders with disabilities. Advocates for a collaborative approach between judges and psychiatrists to ensure fair treatment. Highlights the need for systemic reforms to protect the rights of persons with disabilities in the justice system. Keywords: Disability, Punishment, Legal Reform, Equality, Criminal Offenders